2000
DOI: 10.1093/molehr/6.10.915
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and tissue concentrations of IGF-I in human myometrium and fibroids under different hormonal conditions

Abstract: The expression of insulin-like growth factor-I (IGF-I) was measured at the mRNA and protein level in myometrium and fibroids from women with and without preoperative treatment with a gonadotrophin-releasing hormone (GnRH) agonist for 3 months, from post-menopausal women, from pregnant women and in myometrium from women without fibroid disease. Women with menstrual periods were classified according to the phase of the cycle. In tissues from non-treated premenopausal women, IGF-I mRNA expression was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 28 publications
(19 reference statements)
0
38
0
2
Order By: Relevance
“…It exerts its mitogenic action by increasing DNA synthesis, accelerating the progression of the cell cycle from G-to S-phase, and inhibiting apoptosis (6). Several studies have indicated increased expression of IGF-I mRNA and higher tissue concentrations of IGF-I protein in leiomyomas versus corresponding myometrium (37)(38)(39). Our previous study also found that IGF-I peptide immunolocalized to the leiomyoma cells and the fibroblasts in the bands of intervening connective tissue comprising the extracellular matrix in some leiomyomas; the latter was not seen in the myometrial samples.…”
Section: Discussionmentioning
confidence: 99%
“…It exerts its mitogenic action by increasing DNA synthesis, accelerating the progression of the cell cycle from G-to S-phase, and inhibiting apoptosis (6). Several studies have indicated increased expression of IGF-I mRNA and higher tissue concentrations of IGF-I protein in leiomyomas versus corresponding myometrium (37)(38)(39). Our previous study also found that IGF-I peptide immunolocalized to the leiomyoma cells and the fibroblasts in the bands of intervening connective tissue comprising the extracellular matrix in some leiomyomas; the latter was not seen in the myometrial samples.…”
Section: Discussionmentioning
confidence: 99%
“…Englund et al (2000) reported that leiomyomas taken from premenopausal women contained more IGF-I mRNA than tumors taken from postmenopausal women and that IGF-I concentrations correlated with serum E 2 concentrations (Englund et al 2000). Likewise, Giudice et al (1993) reported that myometrium and leiomyomas taken from the follicular phase of the cycle, when E 2 levels peak, express higher levels of IGF-I transcripts than tumors and myometrium from the luteal phase.…”
Section: Discussionmentioning
confidence: 99%
“…Boehm et al (1990) reported IGF-I mRNAs to be higher in leiomyomas than normal tissue, whereas a study by Gloudemans et al (1990) concluded that no difference existed. Investigations in which tissue samples were grouped according to menstrual cycle reported that leiomyomas contained higher levels of IGF-I message than like-staged myometrium, but these data either failed to reach statistical significance (2-fold) or were marginal (1·1-to 1·4-fold) (Vollenhoven et al 1993, Englund et al 2000. In a study by Giudice et al (1993), IGF-I was expressed by follicular phase leiomyoma and normal myometrium, but small sample size and lack of quantitation made correlation of changes in IGF-I levels with phase of menstrual cycle problematic.…”
Section: Introductionmentioning
confidence: 99%
“…The immunoreactivities for insulin-like growth factor 1 and insulin-like growth factor receptor were significantly higher in leiomyomata than in myometrium (Po0.03 and o0.001), which is consistent with the previous studies. 28,29 It has been shown that AKT and phosphatidylinositol 3-kinase were upregulated in fibroid. 30 Our data showed a similar finding but statistically insignificant due to a large variation ( Figure 2, Table 2).…”
Section: Immunohistochemical Data In the Panelsmentioning
confidence: 99%